Accounting Practices in the Netherlands/Accounting Practices in Sweden/Accounting Practices in Argentina (Book). - Zeff, Stephen A.; McDaniel, C. D. (The Accounting Review, 1964)
Reviews three books on accounting. "Accounting Practices in the Netherlands"; "Accounting Practices in Sweden"; "Accounting Practices in Argentina."